Hollywood economics : how extreme uncertainty shapes the film industry - De Vany, Arthur S. (Contemporary political economy series., 2004)
Movies expected to perform well can flop, whilst independent movies with low budgets can be wildly successful. In this superb new book, De Vany casts his expert eye over all aspects of the business and presents some intriguing conclusions.